2007
DOI: 10.1007/s11240-006-9173-4
|View full text |Cite
|
Sign up to set email alerts
|

Increasing maize seed weight by enhancing the cytoplasmic ADP-glucose pyrophosphorylase activity in transgenic maize plants

Abstract: ADP-glucose pyrophosphorylase (AGPase) plays a key role in regulating starch biosynthesis in cereal seeds and is likely the most important determinant of seed strength. The Escherichia coli mutant glgC gene (glgC16), which encodes a highly active and allosterically insensitive AGPase, was introduced into maize (Zea mays L.) under the control of an endosperm-specific promoter. Developing seeds from transgenic maize plants showed up to 2-4-fold higher levels of AGPase activity in the presence of 5 mM inorganic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…Smidansky et al (2003) described a transgenic rice line in which seed yield and biomass were increased through transformation with a gene encoding a modifi ed maize AGPase that was insensitive to inorganic phosphate. Similar results were obtained from analogous experiments in potato (Sweetlove et al, 1996), wheat (Smidansky et al, 2002;Meyer et al, 2004Meyer et al, , 2007, rice (Sakulsingharoj et al, 2004) and maize (Wang et al, 2007). Sweetlove et al (1996), on the other hand, reported that the transformed modifi ed AGPase gene did not affect the starch content of tubers in spite of the increase in AGPase activity.…”
Section: Discussionsupporting
confidence: 80%
“…Smidansky et al (2003) described a transgenic rice line in which seed yield and biomass were increased through transformation with a gene encoding a modifi ed maize AGPase that was insensitive to inorganic phosphate. Similar results were obtained from analogous experiments in potato (Sweetlove et al, 1996), wheat (Smidansky et al, 2002;Meyer et al, 2004Meyer et al, , 2007, rice (Sakulsingharoj et al, 2004) and maize (Wang et al, 2007). Sweetlove et al (1996), on the other hand, reported that the transformed modifi ed AGPase gene did not affect the starch content of tubers in spite of the increase in AGPase activity.…”
Section: Discussionsupporting
confidence: 80%
“…For example, a mutant Escherichia coli AGPase (glgC-16) with altered allosteric properties was expressed in potato and the rate of starch synthesis increased 35% (Stark et al, 1992). The mutant E. coli enzyme was recently shown to increase maize seed weight 22% to 25% (Wang et al, 2007). AGPase of the transgenic maize seed was shown to be less sensitive to Pi inhibition compared to wild type.…”
mentioning
confidence: 99%
“…In addition, the inhibition of starch biosynthesis was complemented by a massive reduction in the expression of the major storage protein species of potato tubers, supporting the idea that the expression of storage protein genes is in some way connected to carbohydrate formation in sink storage tissues. There are some reports also exist where a mutant Escherichia coli AGPase gene (glgc16) were over-expressed in some plants for enhancing the starch accumulation, such as potato [17] and maize [42].…”
Section: Genetic Engineering Of Potato For Modification Of Carbohydramentioning
confidence: 99%